(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2018)
The problems of compiling the physico-geological model (PGM) of the investigated territory were considered for predetermining the possible complex of geophysical methods for solving tasks. Аs an example, the PGM of Meghri HPP (Armenia) projected hydrotechnical tunnel territory is considered.